5.5-10.5 GHz IR-UWB Pulse Generator for Narrowband Interference Mitigation - Ahmed R., Mohammed; Khalid A. S., Al-Khateeb; Islam, Md. Rafiqul (IEEE, 2012)
An impulse radio ultra wideband (IR-UWB) pulse generator works between 5.5-10.5 GHz for narrowband interference mitigation is proposed. With an average power of -85 dBm/MHz from 0-5 GHz, high interference avoidance has been achieved for a wide range of narrowband systems including Global Positioning System (GPS), Worldwide Interoperability for Microwave Access (WiMAX), Wireless Local Area Network (WLAN) 802.11b and 802.11a. The proposed pulse generator utilizes a 1 GHz sine wave power source to work with the designed half-wave rectifier. The generated pulse width is less than 1 ns, providing a speed of about 1 Gb/s for IR-UWB system with minimum modulation complexity. A passive low pass filter (LPF) is designed with a cutoff frequency of 1.5 GHz works with the circuit up-converter mixer to generate a pulse which matches the Federal Communication Commission (FCC) requirements of UWB. The design has been carried out using Advanced Design System (ADS) software. The proposed pulse generator is supported by different modulation techniques like on-off keying (OOK) and pulse position modulation (PPM).